Hubungan Tingkat Pengetahuan, Pekerjaan Dan Personal Hygiene Dengan Kejadian Penyakit Kusta Di Kecamatan Kunduran Kabupaten Blora Tahun 2015 - Agnes Curnelia, In; Badar Kiswono, Badar Kiswono.S.KM., M.Kes (2016)
Leprosy is a contagious disease that case complex problem. The problem is not only terms of medical, but extends to social, economic, cultural, security and social resilience. Blora leprosy prevalence in the county recorded 94 cases, with as many as 18 types of leprosy PB and as many as 76 people leprosy MB. Of the data of leprosy cases in the PB and MB cases in the district Kunduran 7 people with leprosy PB and 11 people with caes of MB, so that all leprosy patients as many as 18 people. Based of the case of second degree disability in Blora district there are 17 people, in the district Kunduran there were 4 cases of disabled leprosy patient with level 2. This study aims to determine the releationship of the level of knowledge, work and personal hygiene with the incidence of leprosy in the district Kunduran Blora district. This type of research is an analytic obeservational research using case control approach. Samples were taken using total sampling and obtanied a sample of 18 lepers plus control of 36 people suftering from leprosy. Data were analyzed using SPSS using chi square test (X2) with significance level 95%. The results of this study indicate that there is a significant relationship between work and the incidence of leprosy in the district Kunduran Blora district in 2015, there is significant relationship between the knowledge of the incidence of leprosy in the district Kunduran Blora district in 2015, and there is significant relationship between the personal hygieni of the incidence of leprosy in the district Kunduran Blora district in 2015. Keywords : knowledge, work, personal hygiene, the incidence of leprosy